(untitled) (Nordic Journal of African Studies, 2005)
Malaria is a major public health problem in Malawi, under-five children and pregnant women being the most vulnerable. This study, done among the Tumbuka of northern Malawi, details the perceptions about the aetiology, treatment and prevention of malaria in under-five children. One of the major findings is that while Fansidar is the right treatment for malaria, there are delays in seeking the right treatment because of, among other factors, perceptions about the cause of malaria, distances to the health centres, unavailability of drugs in health centres and the perception that antipyretics are the right treatment for febrile illness. While informants were able to relate convulsions in under-five children to malaria, they could however not relate splenomegaly to malaria. For both convulsions and splenomegaly, traditional medicine was the first choice when children suffered from these conditions; children were only taken to the health centre when traditional medicines failed. The problem with malaria is that it can develop from mild illness to serious illness and death within 48 hours; hence the need to seek treatment timely. The need for awareness campaigns can therefore not be over-emphasized.